Crowdsourcing Practices in Academic Libraries in Nigeria - Jacob Kehinde Opele; Cecilia Funmilayo Daramola; Glory O. Onoyeyan (Evidence Based Library and Information Practice)
Objective – In this study, we investigated the utilization of crowdsourcing practices among academic librarians in Nigeria, encompassing all 36 states across the 6 geopolitical zones of the country.